HUBUNGAN CHRONIC ANKLE INSTABILITY DENGAN KESEIMBANGAN DINAMIS PADA PEMAIN SKATEBOARD DI DENPASAR BALI - Dewa Alit Kamayoga; Dedi Silakarma; I Nyoman Adiputra (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2015)
Skateboarders often ignore repetitive injuries that occurred while they were playing.Repetitive injuries that are not handled properly will lead to chronic ankle instability.Chronic ankle instability will lead to a condition where skateboarders will experience anunbalanced dynamic equilibrium as they are skateboarding or while doing dailyactivities. The purpose of this study was to determine the relationship of chronic ankleinstability with dynamic balance of skateboarders in Denpasar, Bali. This study was ananalytical descriptive study with a cross sectional study design. The population of thisstudy was all skateboarders that joined Persatuan Skateboarder Bali (PSB) in Denpasar.Sampling techniques in this study was Non Probability Sampling. Sample size wasobtained using saturation sampling technique. In this study, the number of samples thatmet the inclusion criteria was 60 people. Data analysis using chi-square test obtained aresult p = 0,000 (p<0,05). It can be concluded that there was a significant relationshipbetween chronic ankle instability with dynamic balance.